Contemplative Practice, Doxographies, and the Construction of Tibetan Buddhism: Nupchen Sangyé Yeshé and The Lamp for the Eye in Meditation - Alcalá, Manuel (Religions, 2018)
In this article, I would like to reframe our understanding of the role played by doxographies or classification of views (Skt. siddhānta, Ch. panjiao ??, Tib. grub mtha') in the Buddhist tradition as it pertained to Tibetan attempts at defining and organizing the diversity of Buddhist contemplative practices that made their way into Tibet since the introduction of Buddhism to the Tibetan plateau in the seventh century, all the way up to the collapse of the Tibetan Empire in the ninth century. In order to do that, this article focuses on one such doxography, the Lamp for the Eye in Meditation (bsam gtan mig sgron), composed in the 10th century by the Tibetan scholar Nupchen Sangyé Yeshé. The first part of the article will place Nupchen's text in the larger historical and intellectual context of the literary genre of doxographies in India, China, and Tibet. The second part of the article will argue that Nupchen used the doxographical genre not only as a vehicle for organizing and articulating doctrinal and contemplative diversity, but also as a tool for the construction of a new and original system of Tibetan Buddhist practice known as the Great Perfection' (rdzogs chen). Finally, and as a small homage to the recent passing of the great religious studies scholar Jonathan Z. Smith, I would also like to reflect on the importance that the issues of definition, comparison, and classificationcentral concerns of Nupchen's as well as of Smith's workshave in creating and articulating religious difference.